Decision-making under the EU's social chapter: Discretion and amendments - Laszlo Goerke; Kathrin Piazolo (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
In 1993 the EU created a new procedure for social policy legislation. As the UK objected to its inclusion into the 'Maastricht Treaty1 the Social Chapter was established as separate agreement. A central features is that trade unions and employer organisations, the social partners, can propose legislation. Two legally contentious issues are analysed using simple game-theoretic principles: a) whether Commission and Council are endowed with discretion, b) whether either of them can amend proposals. While discretion restricts the social partners' influence, the right to amend might render the mechanisms laid down in the Social Chapter ineffective.
Keywords: D72; D78; F02; K33; 330; Decision-Making; European Union; Legal Interpretation; Social Chapter